Development of Applications to Prevent Children’s Anemia to Increase Mother’s Knowledge about Anemia in Children - Yuliantisari Retnaningsih; Nur Djanah; Novan Edo Pratama (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Anemia is a health problem that is often found throughout the world and has an impact on the quality of human resources. Nutritional anemia will slowly inhibit the growth and development of intelligence, children will be more susceptible to disease due to decreased immune systems, this will certainly improve the condition of children as successors. Utilizing current technological developments, it is very possible to develop systems that can optimize children's health, especially during the COVID-19 pandemic. The purpose of this study was to know the effect of the application of prevention of anemia in children on mother's knowledge about anemia in children. Quasi-experimental research using pre-post test control group design. Samples were mothers who had children under five in the Puskesmas Banguntapan II, which were divided into two groups (35 intervention groups and 35 control groups). Data analysis with univariate and bivariate. The group was given an application intervention to prevent anemia in children. The control group conducted presented information in accordance with the procedures carried out from the puskesmas with leaflets. Both groups were measured before the intervention and 1 month before the intervention using a questionnaire. The results showed there was a significant increase between the intervention group compared to the control group in the level of mother's knowledge about child anemia (p=0.001). The result is applications increase the effectiveness of mothers’ knowledge about anemia in children, the use of applications is more effective than the use of leaflets in increasing knowledge about anemia.